Pengembangan bimbingan belajar SDN 003 Bukit Kapur di Kelurahan Kampung Baru - Muhammad Nur Faiq; Chairul Chairul; Rian Novri Ramadhan Harahap; Dandi Wahyudi; Ellin Fatikasari; Esi Yuyun Marito Hutauruk; Maya Lestari; Cindy Florentina Sari Hutagalung; Novitasari Novitasari; Siti Asfizura (Unri Conference Series: Community Engagement, 2022)
The very rapid development of technology and its very fast distribution as well as the spread of the Corona virus have resulted in a shift in the function of education in the Kampung Baru community. To achieve this success, it is necessary to instill the discipline of learning from an early age and always give efforts to remind the culture of learning to read and count, especially in terms of literacy and numerization to students at SDN 003 Bukit Kapur. Tutoring can be obtained from each individual who has the aim of helping each student to know himself and be able to act fairly, facilitating students to make skills and understanding in learning. In addition, tutoring can also help solve students' learning problems.